Functional evaluation of pure natural edible Ferment: protective function on ulcerative colitis - Chen, Yanjun; Ye, Shengzhi; Shi, Jiaolong; Wang, Hao; Deng, Guangxu; Wang, Guangxian; Wang, Shijie; Yuan, Qingbin; Yang, Lunan; Mou, Tingyu (Frontiers in Microbiology, 2024)
Purpose: To investigate the therapeutic efficiency of a novel drink termed 'Ferment' in cases of ulcerative colitis (UC) and its influence on the gut microbiota.In this study, we developed a complex of mixed fruit juice and lactic acid bacteria referred to as Ferment. Ferment was fed to mice for 35 days, before inducing UC with Dextran Sulfate Sodium Salt. We subsequently investigated the gut microbiome composition using 16S rRNA sequencing.Result: After Ferment treatment, mouse body weight increased, and animals displayed less diarrhea, reduced frequency of bloody stools, and reduced inflammation in the colon.Beneficial bacteria belonging to Ileibacterium, Akkermansia, and Prevotellacea were enriched in the gut after Ferment treatment, while detrimental organisms including Erysipelatoclostridium, Dubosiella, and Alistipes were reduced.These data place Ferment as a promising dietary candidate for enhancing immunity and protecting against UC.